ROLE OF SOCIAL SUPPORT IN SCHIZOPHRENIA RECOVERY - Dr Sher Ayub; Dr Abid Usman; Dr Abdul Shakoor (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Schizophrenia is a severe illness that changes a person’s thoughts, emotions and behaviour. While medicines help with symptoms, experts now recognize that social support is key to a person’s overall improvement in health, mood and ability to participate in social activities. Objective: To evaluate the impact of perceived social support on recovery outcomes in individuals with schizophrenia, focusing on functional capacity, emotional well-being, and quality of life. Materials and Method: The study was carried out at Khalifa Gul Nawaz Teaching Hospital, MTI Bannu, from January, 2024 to June, 2024. A total of 120 patients between the ages of 18 and 60 with schizophrenia were tested using the Multidimensional Scale of Perceived Social Support (MSPSS) and Recovery Assessment Scale (RAS). The data were studied through SPSS to determine correlations and regression. Results: Among all the support received, family support was the most strongly tied to recovery (r = 0.68, p < 0.01), explaining 42% of the total difference in RAS scores. Support types working together explained the outcomes of 53% of recovery cases. Conclusion: The involvement of a family’s support can help people with schizophrenia recover more effectively, so it is essential to focus on family-centered care plans.